KOMUNIKASI DAKWAH DI LINGKUNGAN VI PASAR 5 MEDAN MARELAN - Hendri Fauza; Neni Nita Wahyuni; Mustika Khairunnisa; Nurul Mawaddah Harahap; Putri Intan Permatasari (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
The da'wah communication pattern is a form or model and style of communication between two or more people in the process of delivering religious messages as well as an invitation to call for goodness. Islamic da'wah is basically an obligation for all Muslims in carrying out their religion, as a religion that calls for good and stays away from evil. In today's modern era, it has become imperative for all preachers to utilize the media and all technologies to facilitate the achievement of the path of da'wah and the target of da'wah. One of the effective communication media is television, because almost all people watch television at this time. This research is descriptive qualitative which aims to conduct in-depth interviews with respondents who have been determined, this data collection is also assisted by conducting interviews with all community members in Marelan. As for the main problem is how the pattern of communication. This study conducted interviews and collected data as well as documentation. This research shows that communication patterns are a different communication model between preaching on television and in direct community audiences that are humanistic, approach to congregations. According to the situation and condition of the audience. The position of communication in Islam is under quite strong pressure for humans as members of society and as creatures of God. In the Qur'an there are many verses that describe the process of communication. One of them is the dialogue that took place for the first time between Allah swt., angels, and humans. The dialogue also describes one of the human potentials given by Allah SWT to humans.